Traditional Chinese Medicine: A promising strategy to regulate inflammation, intestinal disorders and impaired immune function due to sepsis - Wang, Xu-Hua; Xu, Ding-Qiao; Chen, Yan-Yan; Yue, Shi-Jun; Fu, Rui-Jia; Huang, Lu; Tang, Yu-Ping (Frontiers in Pharmacology, 2022)
Sepsis is characterized by a dysregulation immune response to infection leading to life-threatening organ dysfunction. The interaction between intestinal microbiota and sepsis can’t be ignored, furthermore, the intestinal microbiota may regulate the progress of sepsis and attenuate organ damage. Thus, maintaining or restoring microbiota may be a new way to treat sepsis. Traditional Chinese medicine (TCM) plays an important role in the treatment of sepsis through multi-component, multi-pathway, and multi-targeting abilities. Moreover, TCM can prevent the progress of sepsis and improve the prognosis of patients with sepsis by improving the imbalance of intestinal microbiota, improving immunity and reducing the damage to the intestinal barrier. This paper expounds the interaction between intestinal microbiota and sepsis, then reviews the current research on the treatment of sepsis with TCM, to provide a theoretical basis for its clinical application.